Mekanisme Rekrutmen Calon Legislatif Perempuan dalam Pemilihan Legislatif Tahun 2019 (Studi di DPC Partai Kebangkitan Bangsa Kabupaten Malang) - Mahathir Muhammad Iqbal; Ahmad Syaiful Kurniawan (UNIVERSITAS INDO GLOBAL MANDIRI, 2020)
AbstractPolitical parties play a role as a very strategic link between government processes and citizens. Each political party has a different recruitment pattern, where the recruitment pattern of party members is adjusted to the political system it adopts. In recruiting members and candidates for the 2019 legislative elections, DPC of the Malang Regency National Awakening Party provides equal opportunities for all citizens to compete in the selection process of candidates. The theory used is the recruitment of Pippa Norris who uses three indicators, namely: the certification stage, the nomination stage, and the general election stage. The type of approach used is qualitative using the case study method. The results of this study indicate that there are considerations taken by the National Awakening Party DPC to determine female members and candidates based on party regulations regarding the recruitment mechanism of members and candidates. Regarding this, the National Awakening Party DPC gave equal freedom to all citizens, both women and men, to become candidates. This is based on 3 indicators of the recruitment pattern of Pippa Norris, namely: first, the certification stage for candidates, the National Awakening Party DPC provides equal opportunities for everyone to run for party according to party regulations. Second, in the nomination stage, women candidates are given knowledge and skills by being obliged to enter the party underbow organization. Third, the election stage where women candidates are carried by parties to compete in legislative elections. Where women are only used as fulfillment of the 30% quota of women's representation in 2019 legislative electionsKeywords : Recruitment, women, political partiesAbstrakPartai politik memainkan peran sebagai penghubung yang sangat strategis antara proses-proses pemerintahan dengan warga negara. Setiap partai politik memiliki pola rekrutmen yang berbeda, dimana pola perekrutan anggota partai disesuaikan dengan sistem politik yang dianutnya. Dalam melakukan perekrutan anggota dan Caleg untuk pemilihan legislatif tahun 2019, DPC Partai Kebangkitan Bangsa Kabupaten Malang memberikan kesempatan yang sama kepada seluruh warga negara untuk ikut bersaing dalam proses penyeleksian Caleg. Teori yang digunakan adalah rekrutmen dari Pippa Norris yang memakai tiga indikator, yakni: tahap sertifikasi, tahap nominasi, dan tahap pemilihan umum. Jenis pendekatan yang digunakan adalah kualitatif dengan memakai metode studi kasus Hasil penelitian ini menunjukan bahwa adanya pertimbangan yang diambil oleh DPC Partai Kebangkitan Bangsa untuk menetapkan anggota dan Caleg perempuan berdasarkan peraturan partai tentang mekanisme perekrutan anggota dan Caleg. Perihal ini DPC Partai Kebangkitan Bangsa memberikan kebebasan yang sama kepada semua warga Negara baik perempuan maupun laki- laki untuk menjadi Caleg. Ini berdasarkan 3 indikator pola rekrutmen Pippa Norris yaitu: pertama, tahap sertifikasi terhadap Caleg, DPC Partai Kebangkitan Bangsa menyediakan kesempatan yang sama kepada semua orang untuk mencalonkan diri sesuai dengan peraturan partai. Kedua, tahap nominasi, caleg perempuan diberikan pengetahuan dan ketrampilan dengan berkewajiban masuk pada organisasi underbow partai. Ketiga, tahap pemilu dimana caleg perempuan diusung partai untuk bersaing pada pemilihan legsilatif. Dimana perempuan hanya dijadikan sebagai pemenuhan kuota 30% keterwakilan perempuan dalam pileg 2019.Kata kunci : Rekrutmen, perempuan, partai politik